2018
DOI: 10.1016/j.afjem.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory failure requiring mechanical ventilation in critically ill adults in Ghana: A prospective observational study

Abstract: IntroductionRespiratory failure is commonly seen in African emergency centres and intensive care units, but little is known about the need for intubation and mechanical ventilation.MethodsFrom April to October 2017, we recorded the number of patients intubated and ventilated in the emergency centre and intensive care unit at Komfo Anokye Teaching Hospital in Kumasi, Ghana on a daily basis. We assessed patients for presence of acute respiratory distress syndrome (ARDS) using the Kigali Modification of the Berli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In this study, most clinicians preferred the use of low tidal volumes in the ventilator management of ARDS in the ICU, which is a safe and widely accepted standard practice supported by many studies such as Brower et al [16], Walkey et al [19], Papazian et al [20]. Unsurprisingly, a study conducted at Komfo Anokye Teaching Hospital (KATH) by Osei-Ampofo et al [21], where low tidal volume ventilation was not practised, recorded high mortality among patients with ARDS. The effectiveness of non-invasive ventilation in ARDS has been found to decrease with increasing severity of the disease.…”
Section: Clinicians' Practicesmentioning
confidence: 92%
“…In this study, most clinicians preferred the use of low tidal volumes in the ventilator management of ARDS in the ICU, which is a safe and widely accepted standard practice supported by many studies such as Brower et al [16], Walkey et al [19], Papazian et al [20]. Unsurprisingly, a study conducted at Komfo Anokye Teaching Hospital (KATH) by Osei-Ampofo et al [21], where low tidal volume ventilation was not practised, recorded high mortality among patients with ARDS. The effectiveness of non-invasive ventilation in ARDS has been found to decrease with increasing severity of the disease.…”
Section: Clinicians' Practicesmentioning
confidence: 92%
“…Two other articles [22,27] reported that the lack of resources sometimes forces a classification decision to be made on which patients are most likely to survive to the start of mechanical ventilation. This accurately reflects the realities of intensive care and emergency in a resource-limited setting.…”
Section: Optimization Of Resources In Patients With Ards In Emergency...mentioning
confidence: 99%
“…8 However, prone position ventilation (PPV) can greatly promote alveolar recruitment and improve pulmonary ventilatory function, and more than 80% of patients can benefit significantly. 9,10 PPV can change the thoracic pressure gradient and thus correct the abnormal distribution of lung lesions.…”
Section: Introductionmentioning
confidence: 99%
“…However, long‐term supine position ventilation (SuPV) can quickly induce gravitational alveolar collapse, causing compressive atelectasis and pulmonary oedema, aggravating hypoxemia 8 . However, prone position ventilation (PPV) can greatly promote alveolar recruitment and improve pulmonary ventilatory function, and more than 80% of patients can benefit significantly 9,10 . PPV can change the thoracic pressure gradient and thus correct the abnormal distribution of lung lesions.…”
Section: Introductionmentioning
confidence: 99%